1127 Pregnancy outcomes in alemtuzumab trials and registry design. (1st December 2017) - Rog, David; Oh, Jiwon; Chambers, Christina; Fox, Edward J; McCombe, Pamela; Otero, Susana; Margolin, David H; Kasten, Linda; Compston, DAlastair S
Abstract : Pregnancy outcomes in patients in the alemtuzumab MS clinical development program (CAMMS223 and NCT00050778 ; CARE-MS I and NCT00530348 ; CARE-MS II and NCT00548405 ; CAMMS03409 and NCT00930553 ) were evaluated. Patients received 2 alemtuzumab courses in core studies (baseline, 5 days; 12 months later, 3 days), and optional, as-needed retreatment during extension per investigator discretion. Pregnant/lactating patients were treatment-ineligible but remained on study for safety follow-up. By December 31, 2015, 200 pregnancies occurred in 137/972 alemtuzumab-treated women, including 182 completed with known outcomes, 11 ongoing, and 7 unknown outcomes. Of completed pregnancies, 123 (68%) were live births without congenital abnormalities or birth defects; 39 (21%) spontaneous abortions, 19 (10%) elective abortions, and 1 (0.5%) stillbirth (previously reported). There was no evidence of teratogenicity, and the spontaneous abortion rate was comparable with other MS and general populations. Women are recommended to use effective contraception during alemtuzumab infusion and for 4 months after. Real-world data are currently collected by the International Lemtrada Pregnancy Exposure Registry, a prospective, noninterventional, observational safety study enrolling patients pregnant during or within 4 months of alemtuzumab exposure in ≥19 countries. It will evaluate pregnancy outcomes, including monitoring infants for adverse events for 1 year. UK pregnancy cases can be reported to: Neuroresearch.nurse@srft.nhs.uk; phone 0161-206-0534. Study Support: Sanofi and Bayer HealthCare Pharmaceuticals.